Kinetic Alfvén Waves in space plasma environment with κ-electrons - Barik, K.C.; Singh, S.V.; Lakhina, G.S. (My University, 2021)
A resonant instability of kinetic Alfvén waves (KAWs) driven by ion beam is discussed through a theoretical model encompassing Maxwellian background ions and beam ions and non-Maxwellian κ-electrons. The ion beam velocity alone as a source is able to excite the KAWs up to a significant growth. The non-Maxwellian parameter κ impedes the growth of KAWs by restricting the wave unstable region. The effects of other plasma parameters such as propagation angle, temperature of the plasma species, and ion plasma beta on the excitation of KAWs are also examined. The present model can generate waves with frequencies in the range of ≈6.6–51.2 mHz, which are relevant to explaining the observed ultralow frequency waves at auroral ionospheric altitudes. Theoretical model predictions will also be applicable to other planetary environments where ion beams and non-Maxwellian κ-electrons are present.
Keywords: Solar wind, Space plasmas, Alfven waves